Blood Flow Restriction Exercise Attenuates the Exercise-Induced Endothelial Progenitor Cell Response in Healthy, Young Men - Montgomery, Ryan; Paterson, Allan; Williamson, Chris; Florida-James, Geraint; Ross, Mark Daniel (Frontiers in Physiology, 2019)
Endothelial progenitor cells (EPCs) are a vasculogenic subset of progenitors, which play a key role in maintenance of endothelial integrity. These cells are exercise-responsive, and thus exercise may play a key role in vascular repair and maintenance via mobilization of such cells. Blood flow restriction exercise, due to the augmentation of local tissue hypoxia, may promote exercise-induced EPC mobilization. Nine, healthy, young (18-30yrs) males participated in the study. Participants undertook 2 trials of single leg knee extensor (KE) exercise, at 60% of thigh occlusion pressure (4 sets at 30% maximal torque) (BFR) or non- blood flow restricted (non-BFR), in a fasted state. Blood was taken prior, immediately after, and 30 minutes after exercise. Blood was used for the quantification of haematopoietic progenitor cells (HPCs: CD34+CD45dim), EPCs (CD34+VEGFR2+/CD34+CD45dimVEGFR2+) by flow cytometry. Our results show that unilateral KE exercise did not affect circulating HPC levels (p = 0.856), but did result in increases in both CD34+VEGFR2+ and CD34+CD45dimVEGFR2+ EPCs, but only in the non-BFR trial (CD34+VEGFR2+: 269 ± 42 cells·mL-1 to 573 ± 90 cells·mL-1, pre- to immediately post-exercise, p = 0.008; CD34+CD45dimVEGFR2+: 129 ± 21 cells·mL-1 to 313 ± 103 cells·mL-1, pre- to 30 min post-exercise, p = 0.010). In conclusion, low intensity BFR exercise did not result in significant circulating changes in EPCs in the post-exercise recovery period and may impair exercise-induced EPC mobilization compared to non-BFR exercise.